Powerful independent directors. Issue 4 (30th June 2021) - Fogel, Kathy; Ma, Liping; Morck, Randall
Abstract: Shareholder valuations are economically and statistically positively correlated with independent director power, gauged by a composite of social network power centrality measures. Powerful independent directors' sudden deaths reduce shareholder value significantly; other independent directors' deaths do not, consistent with powerful independent directors increasing firm valuations. Further tests associate more powerful independent directors with less value‐destroying mergers and acquisitions, less free cash flow retention, more CEO accountability, and less earnings management. We interpret these findings as more powerful independent directors better detecting and countering CEO missteps because of better access to information, greater credibility in challenging errant top managers, or both.